Micro and Nano Sulfide Solid Lubrication - Wang, Haidou; Xu, Binshi; Liu, Jiajun (Springer Berlin Heidelberg : Imprint: Springer, 2012)
"Micro and Nano Sulfide Solid Lubrication" covers the basic principles of sulfide solid lubrication, which is an important field of tribology, an effective means of reducing friction and wear on machine parts, and is closely related to the broader problem of saving energy and materials. This book discusses the low-temperature sulfuration technology which was first developed in China, as well as the two-step methods for preparing various sulfide lubrication films (coatings) created by the authors, which are described in detail. This book is intended for researchers in the fields of tribology, materials science, mechanical design, and structural design. Dr. Haidou Wang and Binshi Xu are both professors at the National Key Laboratory for Remanufacturing, Academy of Armored Forces Engineering, China; Jiajun Liu is a professor at the Department of Mechanical Engineering, Tsinghua University, China.